Productivity and profitability of basmati rice (Oryza sativa) at farmer’s field under optimal nutrient management practices - KUMAR, SARVENDRA; SHARMA, V K; CHOBHE, KAPIL A; KHAN, M A (The Indian Journal of Agricultural Sciences, 2020)
On farm trials at farmers’ field were conducted for two years (2015-17) to evaluate different fertilizer management options vis-a-vis farmers practice on Basmati rice (Oryza sativa L) (cv. PB-1121) productivity and economics in Rajpura village of Aligarh, UP at two sites having two trials each with distinct soil properties. Results revealed that maximum pooled yield of basmati rice under targeted yield based fertilizer recommendation (TY50) was 4.78 and 4.81 t/ha higher by 33% at site –I and 40% at site-II over farmer practice (FP). From the results, it can be inferred that, around 30-40% basmati rice yield could be increased with targeted yield based fertilizer recommendation. Moreover, the net profits at site-I & II were ₹23486/ha and ₹30905/ha, respectively higher with targeted yield based fertilizer recommendation (TY50), over farmer’s practices (FP). The significant improvement in available nitrogen, phosphorus and potassium was noticed at both sites under targeted yield based fertilizer recommendation in post-harvest soil after two years of trials. The soil microbial biomass carbon and dehydrogenase activity of soil were also enhanced under targeted yield based fertilizer management (TY50) as compared to other fertilizer options studied.